PENGARUH MANAJEMEN ASET TERHADAP PENDAPATAN ASLI DAERAH PEMERINTAH KABUPATEN DAN KOTA DI JAWA BARAT - Widilestariningtyas, Ony (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2016)
Conducted in the local cities and district government in West JavaÂ this research was tookon 2014 period. The phenomenon encountered in the field is the embodiment of autonomy in theform of asset management that gave a less improvement to the local own-source revenue. The objective of this study is to determine how much influence of the asset managementonÂ local own-source revenue Cities and District Local Government in West Java. Research method that used in this research were descriptive and verification method withstatistical testing using Simple Linier Regression with secondary data. Sampling method used isto take all of population called census. The results showed that asset management has a significant effect on the local ownsourcerevenuewithapositivedirection,thatmeanthehigherassetmanagementpoint,thehigherlocalown-sourcerevenuewillbe.ThenThestrengthoftherelationshipwasindicatedashighcorrelation.